Illustrating Business Relevance of Systems Engineering via Storytelling. Issue 1 (26th September 2022) - Siviy, Jeannine; Stolzar, Lauren; McKinney, Dorothy; Sheard, Sarah
Abstract: Many software‐centric organizations do not embrace Systems Engineering, whether lacking awareness or perceiving it too onerous for value delivered. While some embrace Digital Engineering, Design, and Innovation to advance their market position, some continue to experience sub‐optimal results and downstream consequences. These realities show Systems Engineering becoming inconsequential in today's business settings, to the detriment of success and customer value. Effective storytelling, showcasing situational implementation of the right elements of Systems Engineering, can address this. Stories engage, inspire, and create connection. When layered with multiple dimensions and meaning, they become timeless. This paper describes four vignettes about enhancing success in software‐intensive enterprises by leveraging Systems Engineering in context, flexibly and fit for use, and compatibly with other disciplines. The vignettes illustrate how Systems Engineering strengthens performance and positions for flexibility, adaptability, and resilience in a fast‐changing, complex world. The paper concludes with implications for Systems Engineering outreach, leadership, and influence.